ANALISA PERBEDAAN INFORMASI DIAGNOSTIK CT SCAN KEPALA PADA KASUS STROKE ISKEMIK DENGAN PILIHAN KOMBINASI SLICE THICKNESS DAN INTERVAL RECONSTRUCTION - Dwi Yan, Mami; Ardiyanto, Jeffri; Sulaksono, Nanang (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Stroke is a diseas that has a high mortality rate as the third most common disease that causes death in the world. To diagnose the location and type stroke, a neuro imaging examination is need, which is by examining the CT Scan of the head. The purpose of this study was to determine differences in diagnostic information on CT scan of the head in cases of ischemic stroke with a choice combination of 3 mm slice thickness with 1.5 mm interval reconstruction and 2 mm slice thickness with 1 mm interval reconstruction, and to find out which combination is the most optimal in producing diagnostic information in cases of ischemic stroke. Methods: This type of research is quantitative research with experimental approach. The study was conducted at Telogorejo Hospital Semarang. The sampel in this study were 10 patients with expertise results of ischemic stroke. The resultan data was 10 head scan radiographs with ischemic stroke and each radiograph is reformatted with combination of 3 mm slice thickness with 1.5 interval reconstruction and 2 mm slice thickness with 1 mm interval reconstruction. Assesment of diagnostic information data was done by 3 respondents. before data analysis, first kappa test was done to three respondents and then tested wilcoxon. Result :The result of this research is the difference of diagnostic information between combination of 3 mm slice thickness with 1.5 mm interval reconstruction and 2 mm slice thickness with 1 mm interval reconstruction. A combination of 2 mm slice thickness with 1 mm interval reconstruction with mean rank 21.00 is the most optimal combination for head scan with ischemic stroke cases